Mundos possíveis na pós-fotografia: possibilidades de construção da imagem-ficção no instagram - (:unkn) unknown (Universidade Federal do Pampa, 2019)
This dissertation aims at the conceptual investigation of post-photography in the visual narratives produced by cell phone cameras and shared on Instagram social media. Based on Gottfried Wilhelm Leibniz's theory of the possible worlds and anchored in Lubomir Dolezel's appropriation of this theory for the field of literature and Anne Cauquelin for the fields of art and aesthetics, this research is inspired by Philippe Dubois's proposition of the emergence of a post-photographic paradigm from the technical modifications that emerged with the digital turn of the early 2000s, thus becoming a possible predominance of an image-fiction. Thus, this dissertation aims to investigate the possibilities of construction and circulation of image fiction in post-photography present in Instagram social media publications. Considering the possibilities of editing, altering and modifying images through the use of devices, applications, filters and overlay layers that interfere and alter the final photographic product that is shared on Instagram, its problematic proposes to identify how do they express themselves everyday postphotographic productions empowered by the creation of shared fiction images as possible worlds on Instagram social media via mobile devices. Its development is justified as it presents a perspective of approximation of studies on subjects that include post-photography, communication, philosophy, literary theories, arts and aesthetics proposing a reflection on social and cultural practices in times of ubiquitous mobility and their possible repercussions for the professional practice in the photographic area and in the management of communication in mobile media As methodological procedures, it uses Cartography, by Deleuze and Guattari, and Scanning, proposed by Vilém Flusser, to analyze two (2) hashtags and two (2) profiles: #nofilter, #shootermag, @prisma and @VSCO. In the conclusions, based on Manovich's categories for Instagram (casual, professional and projected), the study proposes four additional categories: Image-fiction, Possible worlds, Territory and Instagramism.
Keywords: Fotografia; Instagram (Firma); Mídia social; Comunicação; CNPQ::CIENCIAS SOCIAIS APLICADAS